Goal Orientations And Organisational Outcomes - LEE, JIA-SHEAN (2005)
This research studied the relationship between goal orientations with affective commitment to the organisation and supervisor, as well as with in-role and innovative job performance in organisations. The various dimensions of goal orientations are examined to ascertain their individual influence on these outcomes. The impact of leader-member exchange (LMX) on the relationships between the variables was also examined based on achievement goal and LMX theories.